German S1 Guideline Long-/Post-COVID - Koczulla, A R; Ankermann, T; Behrends, U; Berlit, P; Berner, R; Böing, S; Brinkmann, F; Frank, U; Franke, C; Glöckl, R; Gogoll, C; Häuser, W; et al. (Pneumologie (Stuttgart, Germany), 2022)
The German Society of Pneumology initiated 2021 the AWMF S1 guideline Long COVID/Post-COVID. In a broad interdisciplinary approach, this S1 guideline was designed based on the current state of knowledge.The clinical recommendations describe current Long COVID/Post-COVID symptoms, diagnostic approaches, and therapies.In addition to the general and consensus introduction, a subject-specific approach was taken to summarize the current state of knowledge.The guideline has an explicit practical claim and will be developed and adapted by the author team based on the current increase in knowledge.